2011
DOI: 10.1124/jpet.111.179747
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effects of Antimuscarinic Agents on Bladder Functions in Both Nonhuman Primates and Rodents

Abstract: Both the physiological role of muscarinic receptors for bladder function and the therapeutic efficacy of antimuscarinic agents for overactive bladder syndrome are well documented. We investigated the effect of antimuscarinic agents with different subtype selectivity on urodynamic parameters in nonhuman primates and rodents and compared plasma levels of these agents between species. Anesthetized rhesus monkeys were transurethrally catheterized, and the bladder was infused with saline. Urodynamic parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…Baseline values of urodynamic parameters in vehicle-and vibegron-treated animals are as follows: bladder capacity, 156.8 6 21.6 ml (vehicle), 123.7 6 10.7 ml (vibegron); micturition pressure, 36.7 6 1.6 cm H 2 O (vehicle), 35.5 6 2.8 cm H 2 O (vibegron); bladder compliance, 15.0 6 2.2 ml/cm H 2 O (vehicle), 16.6 6 2.8 ml/cm H 2 O (vibegron). As in the previous study (Nagabukuro et al, 2011), vehicle had no statistically significant effect on any of parameters. Vibegron increased bladder capacity in a dose-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Baseline values of urodynamic parameters in vehicle-and vibegron-treated animals are as follows: bladder capacity, 156.8 6 21.6 ml (vehicle), 123.7 6 10.7 ml (vibegron); micturition pressure, 36.7 6 1.6 cm H 2 O (vehicle), 35.5 6 2.8 cm H 2 O (vibegron); bladder compliance, 15.0 6 2.2 ml/cm H 2 O (vehicle), 16.6 6 2.8 ml/cm H 2 O (vibegron). As in the previous study (Nagabukuro et al, 2011), vehicle had no statistically significant effect on any of parameters. Vibegron increased bladder capacity in a dose-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Cystometry in Rhesus Monkeys. Cystometry was performed as described previously (Nagabukuro et al, 2011). In brief, rhesus monkeys were anesthetized with an intramuscular injection of Telazol (5 mg/kg) or ketamine HCl (20 mg/kg) followed by intravenous constant rate infusion with ketamine HCl (0.2-0.3 mg/kg/min).…”
Section: Methodsmentioning
confidence: 99%
“…3b,c,d). Similar results have been reported using urethane-anesthetized rats and cerebral infarction rats [11,13,24]. As one of putative mechanisms behind these, Yamada et al [25] indicated that imidafenacin excreted in urine may contribute to its selective and long-lasting distribution in the bladder, because imidafenacin showed a significant binding to bladder muscarinic receptors in rats following intravesical injection at concentration levels similar to its urine concentrations after oral administration in rats as well as healthy volunteers.…”
supporting
confidence: 69%
“…Antimuscarinics suppress detrusor smooth muscle activity and inhibit DO; however, urinary urgency and frequency, which are both alleviated by antimuscarinics, are bladder storage symptoms. Because parasympathetic activity is usually absent during bladder storage, antimuscarinics work to improve these symptoms by acting on afferents found within the urothelium 2 .…”
Section: Neuronal Control Of Micturitionmentioning
confidence: 99%